Effective Collegiate Recovery Campuses: Key Elements of Two Exemplars. Issue 170 (5th January 2021) - Castedo, Sierra; Salmeri, Patrice M.; Steiker, Lori K. Holleran
Abstract: This chapter describes two exemplary collegiate recovery programs in order to illustrate the range of variation between programs, while highlighting the common essential elements.